A educação do campo e o processo de rearticulação de escolas públicas do campo - Sudoeste do Paraná – 2015/2020 - Santos, Angelita Cristine do (2021)
This Master’s thesis work finds itself in the Program of Post-Graduation in Education, Master’s degree, Campus Francisco Beltrão/PR, of the State College of Western Paraná (Unioeste), concentration area in Education, Research Line: Culture, Educative Processes and Formation of Teachers. The research’s problematic will center itself in the realization that the changes in naming of Public Schoolsin the state of Paraná located in rural territory, to “field school”, by the Parecer 1011/2010/CEE/CEB/PR, didn’t mean the changing in organizing the contents and shapes to such field public schools occurred in equal terms, nevertheless considering that, in this context, the Field Education was legally recognized as an Education Modality and, its effectuation, could be mediated by the people of the field and its territories. Facing these mismatches, by the year 2015, starts a process of rearticulating somepublic field schools, located in the Southwestern Region of Paraná, in the counties of Enéas Marques, Francisco Beltrão and Verê, with mediations that made possible to put the law to action, in a movement of producing methodological spaces, times and instruments, incorporated, to the Politic-Pedagogical Project and Scholar Regiment, during the process. Taking the movements that had been done in the context of these schools, this research analyses how was the legislation for Field Education operated, in theprocess of rearticulating these public field schools, in the period between 2015 and 2020. The clash of experimented contradictions, with the imminent risk of closure and high rotation of educators, had been hampering the creation of bondsbetween subjects with the educational institution and challenged the collective of the schools to search a way of maintaining themselves articulated. The continued formation showed itself with this potential, thus creating the Network of Formation of Teachers for the Strengthening of Public Field Schools –REFOCAR, aiming to rearticulate the public schools and its subjects, curtailing the closure of these schools and guaranteeing the effectuation of the public politic for the modality of Field Elementary Education, producing movements by the necessities of the realities of the school and its surroundings. The context of this research aimed for analyzing to what extent the teaching practice of the schools, in the concrete way of its pedagogic doings, constitutes itself hasan unfolding and operationalization of the legislation for Field Education currently active in the state of Paraná and its country. The performed analysis allows itself to comprehend that the effectuation of specific practices guaranteed bythe legislationin public field schools, needs the articulation into a collectivity that produces movement and rearticulates bonds to the realities in the context of these schools localized in the rural areas. A process with such potential enables to the Public Schools located in the rural territories, the production of content and shape to the Educational Modality, as a possible way into the perspective of rearticulating itself into the Movement of Field Education.